MINERALOGICAL AND SPECTROSCOPIC STUDY OF NESQUEHONITE SYNTHESIZED BY REACTION OF GASEOUS CO2 WITH MG CHLORIDE SOLUTION - Skliros, V.; Anagnostopoulou, A.; Tsakiridis, P.; Perraki, M. (Bulletin of the Geological Society of Greece, 2016)
Nesquehonite, a hydrous carbonate with promising uses such as building raw material and treatment of wastewaters, was synthesized under low pressure conditions by reaction of gaseous CO2 with Mg chloride solution and it was studied by means of X-Ray Diffraction, optical and scanning/transmission electron microscopy, and FTIR and Raman spectroscopic methods. Synthesized nesquehonite forms elongated fibers, exhibiting transparent to translucent diaphaneity and vitreous luster. It is characterized by high crystallinity. IR and Raman spectroscopy indicated the presence of OHand HCO3 - in the crystal structure of nesquehonite. The nesquehonite synthesis described herein constitutes a potential permanent storage of CO2 emissions.